SAT0079 Characterization of Ra Patients with A DAS28 Response To Adalimumab Therapy by Improvement in Pain: A German Nonintervention Study. (15th July 2016) - Köhm, M.; Scharbatke, E.; Stemmler, E.; Greger, G.; Behrens, F.; Wittig, B.
Abstract : Background: In daily clinical practice, therapeutic responses (eg, Disease Activity Score-28 joints [DAS28]) are not always associated with improvements in pain in patients with rheumatoid arthritis (RA). Objectives: To evaluate pain responses in RA patients with a DAS28 response to adalimumab (ADA) therapy. Methods: We analyzed data from two large German multicenter observational studies of patients with active RA who initiated ADA therapy during routine clinical care. Patients were classified on the basis of significant responses in DAS28 and pain (on a scale of 0=best; 10=worst), as determined by statistical analyses of the critical difference for individual improvement. 1 Patients with a significant DAS28 improvement at month 12 (≥1.8 points from baseline) and significant pain improvement (≥3 points from baseline) were compared with patients with a significant DAS28 response, but no significant reduction in pain. Outcomes included fatigue, patient global assessment (PGA), and physician global assessment (MDGA) (all on a scale of 0=best to 10 = worst) and function as assessed by the Funktionsfragebogen Hannover questionnaire (FFbH; % remaining function). Results: Of 5745 patients in the full analysis set, 1509 patients had available data on pain and a significant DAS28 response at month 12. Of these patients, 1038 had a significant improvement in pain and 471 did not. Baseline characteristics and concomitant medications were similar between the two groups (Table). After 24 months of ADA therapy, both groups had similar swollen and tender joint counts and levels of inflammatory markers. Patients with both DAS28 and pain responses had better functional status at month 12 than patients without an improvement in pain (mean FFbH=76.0% vs 68.8%; P <0.0001), despite lower mean baseline values (56.8% vs 63.8%). Significant differences ( P <0.0001 for all) in favor of patients with pain responses were also observed in mean values for fatigue (2.8 vs 4.2), PGA (3.0 vs 4.5), and MDGA (2.3 vs 2.9) at month 12. Conclusions: Approximately two-thirds of patients with a significant therapeutic response to ADA at month 12 also have a significant improvement in pain. There were no obvious differences in baseline characteristics between patients with or without improvements in pain. Patients with improvements in both DAS28 and pain have significantly less fatigue and significantly improved function and global disease activity at month 12 compared with patients who have a DAS28 response, but no improvement in pain. References: Behrens F et al. Arthritis Care Res. 2013;65:1608–16. Disclosure of Interest: M. Köhm Grant/research support from: AbbVie, Pfizer, Janssen, Speakers bureau: Janssen, MSD, E. Scharbatke Grant/research support from: AbbVie, Chugai, Speakers bureau: AbbVie, E. Stemmler Employee of: AbbVie, G. Greger Employee of: AbbVie, F. Behrens Grant/research support from: Pfizer, AbbVie, Janssen, Consultant for: Pfizer, Janssen, Chugai, Speakers bureau: MSD, Roche, Pfizer, Janssen, Chugai, B. Wittig Employee of: AbbVie